HUBUNGAN AKTIVITAS FISIK DENGAN TINGKAT KESEGARAN JASMANI KELAS X IPS 3 SMA NEGERI 1 BENGKALIS - Raudah, Ayu; Ramadi, Ramadi; Mandan, Ali (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The purpose of this research is to determine the relationship between physical activity and the level of physical fitness for class X IPS 3 SMA Negeri 1 Bengkalis. This type of research is a correlation research, which wants to see the relationship between the independent variable and the dependent variable. Based on the results of the research and discussion that the author has described, it can be concluded from the results of data analysis that it can be seen that the data from filling out the PAQ-questionnaire A by class X IPS 3 at SMA Negeri 1 Bengkalis for the academic year 2020/2021, from 30 students (100%) there were 0 students (0%) in the very high category, 0 students (0%) in the high category, 10 students (33 ,33%) in the medium category, 20 students (66.66%) in the low category and 0 students (0%) in the very low category. And the data on the results of the physical fitness of class X IPS 3 students at SMA Negeri 1 Bengkalis for the Academic Year 2020/2021, (100%) there are 30 students (16.66%) in the very good category, 6 students (20%) in the good category, 14 students (46.66%) in the moderate category, 4 students (13.33%) in the poor category and 1 student (3.33%) in the very poor category. The results of the test study can be concluded that there is a significant relationship between physical activity and the level of physical fitness for class X IPS 3 SMA Negeri 1 Bengkalis for the academic year 2020/2021. With rx.y = 0.433 > r table : 0.374 it means that there is a significant relationship between physical activity and physical fitness. It can be concluded that the higher the physical activity carried out by Class X IPS 3 SMA Negeri 1 Bengkalis, the higher the level of physical fitness. Physical fitness obtained from regular physical activity is expected to be able to make school-age children able to carry out daily tasks without experiencing fatigue, so that these students can achieve optimal performance at school and outside of school.Key Words: Physical Activity, Physical Freshness